2010
DOI: 10.1111/j.1532-950x.2010.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Acetabular Cup Implantation in Cementless Total Hip Arthroplasty

Abstract: Medial positioning of the acetabular cup does not appear to compromise acetabular implant-pelvic stability under normal physiologic loads. Because arthroplasty candidates often have abnormal acetabular architecture, mechanical properties of the cup placed in acetabula without a dorsal rim should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(37 reference statements)
3
6
0
Order By: Relevance
“…Our results suggest that this approach may not be necessary, as we suspect the loads at failure were not compromised by loss of DAR to a clinically significant degree. In a study of medially displaced BFX cups in normal canine hemipelves [ 17 ], loads at failure were comparable to the loads observed in our cadaveric testing, both of which were well above the physiologic range. Based on these findings, we do not routinely advocate reaming through the medial wall as long as the cup is well engaged between the cranial and caudal acetabular margins, regardless of DAR bone stock.…”
Section: Discussionsupporting
confidence: 78%
“…Our results suggest that this approach may not be necessary, as we suspect the loads at failure were not compromised by loss of DAR to a clinically significant degree. In a study of medially displaced BFX cups in normal canine hemipelves [ 17 ], loads at failure were comparable to the loads observed in our cadaveric testing, both of which were well above the physiologic range. Based on these findings, we do not routinely advocate reaming through the medial wall as long as the cup is well engaged between the cranial and caudal acetabular margins, regardless of DAR bone stock.…”
Section: Discussionsupporting
confidence: 78%
“…In both groups, the Zurich Cementless acetabular cup sustained compressive loads 12 times greater than the expected force produced during normal activity in the dog (300 N) . This is similar to findings for the BFX Cementless acetabular cup, which sustained loads 10 times that of normal activity in the dog, when acetabular cups were impacted to, and beyond, the medial acetabular wall …”
Section: Discussionsupporting
confidence: 71%
“…18,19 This is similar to findings for the BFX Cementless acetabular cup, which sustained loads 10 times that of normal activity in the dog, when acetabular cups were impacted to, and beyond, the medial acetabular wall. 20 We defined failure mode as cup displacement or pelvic fracture. Clinically, cup displacement can result from inappropriate cup positioning, incomplete impaction, poor dorsal coverage of the implant, or inadequate bony support.…”
Section: Discussionmentioning
confidence: 99%
“…For cementless canine total hip replacement, the collarless, tapered stem design (BFX system, Biomedtrix) has the longest history and is widely studied. 4,[19][20][21][22] Although clinical results for this implant system are generally good, fixation of cementless femoral components in certain breeds is a clinical challenge due to the lack of taperlock between implant and bone on the endosteal surface. In the current in vitro study using consistently sized femurs (CFI of 1.8-2.4) and a combined loading protocol showed that this design was biomechanically comparable and effective under simulated canine gait for a limited number of loading cycles.…”
Section: Discussionmentioning
confidence: 99%